Determinants of taxpayer compliance in Islamic micro small medium enterprises - Wiwik Tiswiyanti; Nela Safelia; Wirmie Eka Putra; Fredy Olimsar (Universitas Islam Negeri Walisongo Semarang, 2022)
Purpose - This study aims to determine the effect of understanding the tax payment mechanism and tax sanctions on taxpayer compliance and the impact of understanding the tax payment mechanism on taxpayers with tax sanctions as a mediating variable in Islamic Micro Small and Medium Enterprises (MSMEs) in Batanghari Jambi Province.Method - This research is a quantitative descriptive study using primary data and a Likert scale. The population in the survey was 1,236 Islamic MSMEs. Using purposive sampling, 56 samples met the criteria, and 46 samples could be processed and used with the SEM Wrap-PLS 0.7 analysis tool.Result - The results of the study found, in a direct relationship, understanding the tax payments mechanism and tax sanctions can have a positive influence on taxpayer compliance. Mediation is partial (part mediation), meaning that the predictor, a variable understanding of the tax payment mechanism, can affect taxpayer compliance without going through the tax sanctions variable.Implication - The implications of the results of the study found that the taxpayer’s understanding of the tax payment mechanism and tax sanctions can have a positive influence on taxpayer compliance. The government as a tax apparatus can improve and carry out its functions properly, providing guidance, service, and supervision of taxpayers, so that taxpayer compliance can continue to be improved.Originality - This study uses tax sanctions as a mediating variable. As far as researchers know, it has never existed in previous studies, and the study results found that the mediation that occurred was partial.